1996
DOI: 10.1109/10.508541
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cerebral blood flow autoregulation in neonates

Abstract: The dynamic response of cerebral autoregulation to spontaneous changes in arterial blood pressure (ABP) is described by the relationship between cerebral blood flow velocity (CBFV) and resistance-area product (RAP). CBFV was measured with Doppler ultrasound in the middle cerebral artery and ABP with an intra-arterial catheter in 66 neonates. Spontaneous changes in mean ABP were automatically detected and the maximum derivative was used to synchronize the coherent averaging of corresponding CBFV and RAP transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 36 publications
4
61
2
Order By: Relevance
“…This question warrants further study. Surprisingly, we found no association between acid-base status, oxygen or carbon dioxide levels, and cerebral pressurepassivity, given the known cerebral vasoreactive effects of blood gases, particularly carbon dioxide (10,20,21). However, this lack of association is likely related to the fact that blood gases were measured intermittently as opposed to our continuous and prolonged hemodynamic measurements.…”
Section: Discussioncontrasting
confidence: 52%
“…This question warrants further study. Surprisingly, we found no association between acid-base status, oxygen or carbon dioxide levels, and cerebral pressurepassivity, given the known cerebral vasoreactive effects of blood gases, particularly carbon dioxide (10,20,21). However, this lack of association is likely related to the fact that blood gases were measured intermittently as opposed to our continuous and prolonged hemodynamic measurements.…”
Section: Discussioncontrasting
confidence: 52%
“…1). In other words, the model reflects myogenic regulatory mechanisms but not regulation of metabolic origin (26,34). To take the possibility of myogenic regulation into account, it would be necessary to extend the model represented by Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study of healthy adult subjects exposed to both acute and long-term elevation of environmental carbon dioxide found that static autoregulation was impaired initially, but, after 3 days of exposure, autoregulation was unaffected (24). Clinical studies of neonates, which used the static autoregulatory index, have concluded that hypercapnia impairs autoregulatory reactivity in these patients (13,18). Finally, laboratory studies of acute hypercapnia in the newborn piglet and rat and the adult cat also have reported that hypercapnia impairs autoregulation (19,21,25).…”
Section: Discussionmentioning
confidence: 99%